Clinical Characteristics and Treatment Patterns of Open Hand Fractures in the Pediatric Population. Issue 5 (6th May 2023) - Parrado, Raphael H.; Foster, Lukas; Gilbert, Megan; Movtchan, Nellie; Sayrs, Lois; Khoury, Emily; Ballan, Wassim; Schaub, Timothy
Abstract : Background: Open hand fractures are one of the most common injuries in the pediatric population. These injuries are at higher risk of infection, especially in cases of frank contamination. Several studies on adult hand fractures are available in the literature; however, pediatric open hand fractures have yet to be extensively studied. This study aimed to define pediatric open hand fracture's demographics, clinical characteristics, and treatment patterns. Methods: Using the Protected Health Information database, pediatric patients (<18 y old) with the diagnosis of open hand fracture from June 2016 to June 2018 were extracted. Demographic, treatment, and follow-up data were collected. Clinical outcomes included readmission and postoperative infection rates. Results: There were a total of 4516 patients who met the inclusion criteria; the median age was 7 years (interquartile range: 3 to 11); 60% males; 60% white. Displaced fractures occurred in 74% of patients, with the right hand (52%) and middle finger (27%) predominance. The most common mechanism of injury was a crushing injury in-between objects (56%). Associated nerve injury occurred in 78 patients (4%) and vascular injury in 43 patients (2%). Open reduction and internal fixation were performed in 30% of patients. Cephalosporins were the most commonly prescribed antibiotics (73%), followed by aminopenicillins (7%). Nine patients had complications related to surgical intervention (0.2%), and postoperative infection occurred in 44 patients (1%). Conclusions: Pediatric open hand fractures most often occur during childhood and more frequently in males. These fractures tend to be more distal and displaced; reduction and fixation are required in one-third of the cases. Despite the absence of treatment guidelines and variability, this injury exhibits low complication rates. Level of Evidence: Level III, retrospective study.